A aposição e a determinação/ especificação como estruturas nominais de inserção sob a perspectiva da Semântica Enunciativa - Emiliana da Consolacao Ladeira (2018)
The thesis that guides this work is that syntactic structures such as the aposto, adnominal adjuncts, nominal complements, adjective clauses and some adverbial adjuncts have very approximate semantic behavior and, therefore, can be treated, semantically, as Nominal Insertion Structures (ENI). In this way, we maintain that they have essential enunciative role in the construction of the sense of the sentences in which they appear, acting decisively and argumentatively in the construction of the meaning of these statements. From the analysis of some sentences, we propose, according to the theoretical perspective of Semantics of Enunciation, a closer look at these ENIs. For this purpose, we rely mainly on the theorists Oswald Ducrot, Marion Carel, Eduardo Guimarães, Priscila Lacerda and Luiz Francisco Dias, using their concepts such as argumentation, memorable semantic domain, enunciative axes, enunciative convergences, nominal formation, pertinence enunciative and referential. With this, we defend the idea that, in function of the referential present in the nominal formations through the ENIs, the announcer argues and guides the interlocutor in the construction of the meaning, of the meaning of the statements that it produces. These structures, if in syntactic terms - especially the wager - are treated as "accessory", in semantic terms they are so essential that they are able to modify / change the understanding of the meaning of the sentence of which they are part.